Transport of cytoplasmic particles catalysed by an unconventional myosin in living Drosophila embryos. - Mermall, V.L.; McNally, J.G.; Miller, K.G. (Nature, 1994)
Myosins are actin-activated ATPases that are able to translocate along actin filaments using energy derived from ATP hydrolysis. Non-muscle cells contain conventional myosins, which are similar in sequence and structure to muscle myosin, and a number of unconventional myosins whose head sequences are similar but tail sequences are unrelated to conventional myosins. The myosin superfamily currently consists of nine classes; Drosophila 95F is an unconventional myosin and the original member of class VI, which includes a homologue found in pig kidney. Some unconventional myosins have been suggested as mediators of some types of intracellular transport, but there is little direct evidence for this function (but see ref. 6). We have observed transport of cytoplasmic particles in live Drosophila embryos in three dimensions using computational optical sectioning microscopy. We present here evidence that this transport is actin-based, ATP-dependent and catalysed by one such unconventional myosin, the 95F myosin. This is, to our knowledge, the first direct observation of transport catalysed by an unconventional myosin in living cells.